Implementation of the Local Sundanese Character of Gapura Pancawaluya in the Merdeka Curriculum in History Subjects - Fiky Arista; Miftahuddin Miftahuddin; Danu Eko Agustinova (Universitas Hamzanwadi, 2026)
Gapura Pancawaluya is a local character education concept implemented in West Java. Gapura Pancawaluya contains five characters expected by the West Java education office to be in students at school, namely cageur (healthy), bageur (good), bener (correct), pinter (smart), tur singer (skilled). The characters contained in Gapura Pancawaluya can be implemented in schools with habituation activities related to character education in the Merdeka curriculum. However, in reality, schools face challenges in aligning the Gapura Pancawaluya program with the material in history subjects. This study aims to implement the Gapura Pancawaluya program and to develop history learning grounded in the local character of Gapura Pancawaluya within the Merdeka curriculum. This study uses a descriptive qualitative method that involves interviews with experts and the analysis of library sources such as books, journals, and scientific articles. The results of this study indicate a relevance between the local character of Gapura Pancawaluya and the character education contained in the Merdeka curriculum. Furthermore, the values embodied in the Gapura Pancawaluya can also be incorporated into history lessons within the Merdeka Curriculum. Therefore, history lessons that implement the Gapura Pancawaluya become more meaningful because they are accompanied by the instillation of moral values ​​embedded in each step of the classroom. Therefore, this research can contribute to and inspire teachers in developing contextual history learning tools based on local character.